Morphological traits, niche-environment interaction and temporal changes in diatoms. (February 2022) - Kléparski, Loïck; Beaugrand, Grégory; Edwards, Martin; Schmitt, François G.; Kirby, Richard R.; Breton, Elsa; Gevaert, François; Maniez, Emeline
Highlights: Diatoms phenology is controlled by the niche-environment interaction resulting from changes in morphological traits. Cell shape is a key adaptation that confers to each species a unique niche and a place in the sequence of annual succession. As morphology influences long-term changes in abundance, current biogeochemical models should consider cell shape. Abstract: Annual phytoplankton succession is a key ecological phenomenon that drives marine species' life cycles and energy flows within marine ecosystems. Identifying processes that control annual succession is critical to anticipate climate-induced environmental perturbations of this phenomenon and the consequences upon ecosystem functioning. Here, we demonstrate that diatoms in the North Sea undergo strong morphological changes throughout the year and that species with similar phenology possess comparable morphological traits (e.g. cell elongation) and ecological niches. The spring and autumn periods appear to be dominated by oblates (flattened cells) whereas the summer period is dominated by prolates (elongated cells). Elongation of the cell shape enhances buoyancy and confers a selective advantage in stratified low-nutrient waters typical of summer without changing a diatom's surface area/volume ratio or its ability to absorb nutrients. Diatom shape thus appears to have evolved as a key adaptation to a specific environment and confers upon a species its specific niche and phenology, and therefore its place in the sequence of annual succession. As a result, shape influences temporal changes in the abundance of diatoms and their putative response to environmental forcing. We suggest that biogeochemical and earth-system models should include diatom cell shape as a parameter in order to improve model predictions and help our understanding of the consequences of climate change on marine ecosystems.